Protonated Alginate Adsorbent For Cerium(III) Ions Adsorption - Abdul Mu'iz, Fakhri
Cerium is a rare earth metal that has many uses, one of that uses is in the manufacture of electronic materials. In obtaining cerium metal has an expensive cost, result many waste and harmful to the environment. Scientists are trying to find methods of collection and separation of rare earth metals at a relatively cheap and environmentally friendly. Calcium alginate (CA) and barium alginate (BA) are biosorbent which can be used to uptake the metal ions because the structure of alginate containing a carboxylic group. To improved adsorbent performance, CA and BA were soaked in 1 M solution of HNO3 for 24 hours so resulted protonated calcium alginate (CAP) and protonated barium alginate (BAP). Alginate-based adsorbent which has been synthesized (CA, BA, CAP, and BAP) were characterized by Fourier Transform Infrared (FTIR) and Scanning Electron Microscope (SEM). Then the adsorption studi of Ce3+ ions was done by using batch studies. Studi of various adsorption parameters was done such as initial concentration of Ce3+ ions, pH, contact time, and adsorbent mass. The results showed that the optimum contact time CA and BA occurs at the contact time of 3 hours, while the optimum time for the CAP and BAP occurs at the contact time of an hour. The initial concentration variation in CA and CAP indicated that achieve optimum adsorption on the initial concentration around 100 mg/L, while the BA and BAP indicated that achieve optimum adsorption on the initial concentration around 50 mg/L. Optimum adsorption capacity achieved at CA and BA to be about 25.87 mg/g and 16.78 mg/g, while the CAP and BAP optimum adsorption capacity increased to be about 48.57 mg/g and 42.76 mg/g. The uptake performance of Ce3+ ions on protonated alginate showed better than non-protonated alginate. Adsorption percentage increased with increasing pH from 3 to 4.5, while the adsorption percentage pH>4.5 tended to be constant. The adsorbent mass could be regenerated effectively using 0.05 g adsorbent. Ce3+ ions adsorption process is pseudo second-order following the Langmuir adsorption isotherm equation.